2000
DOI: 10.5144/0256-4947.2000.324
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Consumption and Development of Resistance among Gram-Negative Bacilli in Intensive Care Units in Oman

Abstract: Since the discovery of antimicrobial agents, microorganisms have developed virtually unlimited resistance to them.1 Hospitals and particularly intensive care units are an important breeding ground for the development of antibiotic-resistant bacteria. This is the consequence of heavy antibiotic use. In addition, a high-density patient population in frequent contact with health care staff and the attendant risk of cross-infection contributes to the spread of antibiotic-resistant micro-organisms. This in turn inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
3
9
0
2
Order By: Relevance
“…These findings are in agreement with those of the study conducted by Streit et al in North America (Streit et al, 2004). However, in a report from Oman, Escherichia coli and Pseudomonas aeruginosa were the pathogens most commonly found in the urinary and respiratory tracts of ICU patients (Al-Lawati, Crouch, Elhag, 2000). Whereas, Klebsiella and Pseudomonas were the microorganisms most commonly found in the urine of patients admitted to the ICU of Imam Khomeini Hospital in Tehran (Hadadi et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in agreement with those of the study conducted by Streit et al in North America (Streit et al, 2004). However, in a report from Oman, Escherichia coli and Pseudomonas aeruginosa were the pathogens most commonly found in the urinary and respiratory tracts of ICU patients (Al-Lawati, Crouch, Elhag, 2000). Whereas, Klebsiella and Pseudomonas were the microorganisms most commonly found in the urine of patients admitted to the ICU of Imam Khomeini Hospital in Tehran (Hadadi et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the resistance rate to cephalosporins (79.5%-87.8%) was comparable to that in Iran (Hadadiet al, 2008), but higher than reported in foreign studies (Gunseren et al, 1999;Al-Lawati, Crouch, Elhag, 2000;Glupczynski et al, 2001;Patzer, Dzierzanowska,Turner, 2002;Gonlugur et al, 2004;Karlowsky et al, 2003;Meric et al, 2005). C u r r e n t r e s u l t s a l s o s h o w e d t h a t 2 5 .…”
Section: Discussionsupporting
confidence: 63%
“…The rates of imipenem susceptibility in our study were different from those reported in previous studies showing that the isolates of Klebsiella spp. and E. coli were fully susceptible to imipenem (30,31). The cause of these differences may be due to higher carbapenem prescription for patients in our study hospital and subsequently the emergence of carbapenem-resistant strains.…”
Section: Discussionmentioning
confidence: 81%
“…7,8 Bila antibiotik diberikan berlebihan, tidak adekuat, monoton (satu jenis terus menerus) maka akan mengurangi efektifitasnya sehingga menimbulkan resistensi terutama bakteri Gram negatif. 1,9 Bakteri Gram negatif yang paling sering diisolasi di ICU anak adalah Pseudomonas aeruginosa, Escherichia coli, Enterobacter cloacae, dan Klebsiella pneumoniae. Sumber bakteremia tersering adalah infeksi saluran kemih dan pneumonia.…”
unclassified